PENGARUH TINGKAT EFEKTIVITAS PERPUTARAN KAS, PIUTANG, DAN MODAL KERJA TERHADAP RENTABILITAS EKONOMI PADA KOPERASI PEDAGANG PASAR GROGOLAN BARU (KOPPASGOBA) PERIODE 2016-2020: Dibuat Oleh Vivi Puji Astuti, Yohani, Muh. Fithrayudi Triatmaja - Fithrayudi, Muhammad; Yohani, yohani; pujiastuti, vivi (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
This study aims to test and analyze the effect of effectiveness of cash turnover, receivables,and working capital on economic rentability in the New Grogolan Market Traders Cooperative of Pekalongan City from 2016 to 2020. The method used in this study was quantitative research method with documentation techniques and analyzed used multiple linear regression analysis. The results of this study showed (1) the effectiveness of cash turnover has no significant effect on economic rentability, (2) the effectiveness of receivables turnover has no significant effect on economic rentability, (3) the effectiveness of working capital turnover has a positive and significant effect on economic rentability, and (4) there is a positive and significant effect on the effectiveness of cash turnover, receivables, and working capital together on economic rentability. Keywords: Turnover of cash, turnover of receivables, turnover of working capital, and economic rentability.